2007
DOI: 10.1097/01.tp.0000250730.30715.63
|View full text |Cite
|
Sign up to set email alerts
|

Dried Blood Spot Measurement of Tacrolimus Is Promising for Patient Monitoring

Abstract: The usefulness of dried blood spot (DBS) sampling for therapeutic drug monitoring of tacrolimus was investigated with renal transplant patients. There was no significant difference between the concentrations (ranging 3.33-53.9 mug/l) of 34 samples of 26 stable renal transplant outpatients, measured both after venous and DBS sampling. DBS sampling is easy to perform because concentrations with and without nurse assistance did not significantly differ. No significant difference was found between tacrolimus conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 6 publications
0
37
0
Order By: Relevance
“…Recently, a method for measurement of tacrolimus level, based on DBS and high-performance liquid chromatography tandem-mass spectrometry (HPLC-MS), has been developed [5]. Preliminary results showed that DBS is promising for routine tacrolimus monitoring of stable renal transplant recipients [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a method for measurement of tacrolimus level, based on DBS and high-performance liquid chromatography tandem-mass spectrometry (HPLC-MS), has been developed [5]. Preliminary results showed that DBS is promising for routine tacrolimus monitoring of stable renal transplant recipients [6].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with previously described LC-MS/MS assays to quantify tacrolimus in dried bloods spots [29][30][31][32][33][34]36,39,41,42 , the present assay matches or exceeds their performance in terms of lower limit of quantification, extraction recovery, accuracy and precision while avoiding potentially risky concepts such as one-step protein precipitation procedures and ultra-short chromatography times, which usually give acceptable results during the validation based on blood samples from healthy individuals. However, transplant patients are a highly complex group of patients who have diseases that affect the composition of blood and who take multiple medications.…”
Section: Discussionmentioning
confidence: 99%
“…After a simple finger stick the patient collects a blood drop on a special filter paper card and after the blood spot has dried, it can be mailed to a central laboratory for analysis of tacrolimus and any other immunosuppressant that the patient may currently be taking. This has become possible due to the development of highly sensitive and specific LC-MS/MS assays for the quantification of tacrolimus and other immunosuppressants in very small blood volumes such as dried blood spots (typically 20 µl of blood) 25,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] . Another advantage is that minimally invasive, low volume sample collection strategies such as dried blood spots greatly facilitate therapeutic drug monitoring and pharmacokinetic studies in small children 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The potential applications of this technology are broad and include field studies in resource-limited settings and the use of patient-self collected specimens that could facilitate monitoring for patients who do not have convenient access to phlebotomy facilities or who are unwilling to undergo venipuncture. This could be particularly relevant for transplant patients, since DBS have also been shown to be suitable for assessing levels of immunosuppressant medications (20). Thus, theoretically, two of the most commonly monitored analytes in transplant patients (immunosuppressant-drug levels and viral load) could potentially be assessed in patient selfcollected DBS samples that are sent to central laboratory facilities using the standard United States mail system.…”
Section: Discussionmentioning
confidence: 99%